Disease burden of psittacosis in the Netherlands. Issue 3 (24th January 2018) - de Gier, B.; Hogerwerf, L.; Dijkstra, F.; van der Hoek, W.
Abstract: Psittacosis (infection with Chlamydia psittaci ) can have diverse presentations in humans, ranging from asymptomatic infection to severe systemic disease. Awareness of psittacosis and its presentations are low among clinicians and the general public. Therefore, underdiagnosis and thereby underestimation of the incidence and public health importance of psittacosis is very likely. We used the methodology developed for the Burden of communicable diseases in Europe toolkit of the European Centre for Disease Prevention and Control, to construct a model to estimate disease burden in disability-adjusted life years (DALYs) attributable to psittacosis. Using this model, we estimated the disease burden caused by psittacosis in the Netherlands to have been 222 DALY per year (95% CI 172–280) over the period 2012–2014. This is comparable with the amount of DALYs estimated to be due to rubella or shigellosis in the same period in the Netherlands. Our results highlight the public health importance of psittacosis and identify evidence gaps pertaining to the clinical presentations and prognosis of this disease.